Café verde almendra. Análisis de competitividad de la empresa café nativo Colombia en Danville, New Hampshire, Estados Unidos. (2023)
The development of this research monograph provides a market analysis of potential customers interested in consuming almond green coffee in Danville, New Hampshire, this study is very important to examine the level of competitiveness of Café Nativo Colombia. The overall objective is to identify market opportunities for the Colombian company Café Nativo Colombia based in Danville, New Hampshire, through competitive analysis, such as PESTEL and DOFA. The development of this monograph takes into account the competitiveness of the coffee market in terms of exports from Colombia to the United States, which allows a comparative analysis through this analysis in which databases of university libraries and other web sources are referenced, documentary research carried out to contribute to the development of the methodology used for this project, presented as a mixed study (qualitative and quantitative). F